Insecticidal Activity, Toxicity, Resistance and Metabolism of Pyrethroids: a Review - Ashutosh Singh; Abhishek Singh; Preeti Singh; Archana Chakravarty; Akhilesh Singh; Priti Singh; Mahendra Kumar Mishra; Vivek Singh; Atul Kumar Srivastava; Himanshu Aggarwal; Suresh Sagadevan (Science and Technology Indonesia, 2022)
Pyrethroids are synthetic or man-made versions of natural pyrethrins discovered in the flowers of a plant species of the Compositae family called "Chrysanthemum cinerariaefolium". The plant was transported into Europe and America after it was discovered in the Near East. Commercial insecticides such as pyrethrin and synthetic pyrethroid are available. These are used to control agricultural pests as well as non-agricultural insects. They are also commercially used in personal care items such as shampoo and as a scent in insect repellent to boost efficacy and persistence in the environment, these insecticides are frequently combined with additional chemicals in diverse formulations, known as synergists. Nerve toxins, known as pyrethroids, although their chemical mechanism of action is unknown. Pyrethroids are neurotoxins, which interfere with the messages sent along nerves by maintaining sodium and chloride channels in an open position. This review presents perspectives, commercial uses and other useful characteristics features of pyrethroids based on human benefits and environmental friendly